Development of Counting Board Media in Class II Mathematics Learning Subject SDN 06 Rantau Alai - Tarisa Tarisa; Adrianus Dedy; Allen Marga Retta (Universitas Muhammadiyah Enrekang, 2024)
Counting board media is a tool to attract students' learning attention. With one of the supporting subjects, namely mathematics. However, learning math in elementary school (SD) is very feared by students and is considered difficult even though learning math is very easy when we already know the method. This study uses development research or research and development. In this study the number of subjects was 22 students. This media was developed using the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. Data collection was carried out by observation, validation questionnaire sheet, and student response questionnaire sheet. This research produces counting board media which is a real learning media and there are animated images. The data analysis technique was carried out by analyzing validity using a validation questionnaire sheet addressed to experts, and analyzing practicality using student response questionnaires. The results of data analysis of the development of counting board media in mathematics learning subjects conducted and developed by researchers are categorized as very valid from the validation questionnaire sheet with an average of 92%, the counting board media in mathematics learning subjects developed are categorized as very practical from the aspect of teacher response with an average of 88% and small group questionnaire sheets in trials with an average value of 89.5%. The counting board media in mathematics learning subjects developed was categorized as effective in the posttest test of students with an average of 86%. Based on the results of validation and trials, it is concluded that the counting board media in mathematics learning subjects is suitable for use in the learning process and can be an attractive alternative for students.